Hope as a predictor for COVID-19 vaccine uptake in the US: a cross-sectional survey of 11, 955 adults. Issue 5 (30th November 2022) - Adam, Maya; Mohan, Diwakar; Forster, Sebastian; Chen, Simiao; Gates, Jennifer; Yu, Fengyun; Bärnighausen, Till
ABSTRACT: Widespread vaccine uptake is critical for ending the COVID-19 pandemic. As public health officials focus on overcoming vaccine hesitancy, simultaneously boosting hope may be equally important in the US. We analyzed data from an online cross-sectional survey conducted in June 2021. Participants were 11, 955 US adults (ages 18–83) of various ethnicities, living in urban and rural settings. Of these, 71.3% had some college education. Mean age was 32.3 years and 72.4% reported being vaccinated against COVID-19. Main measures were COVID-19 self-reported vaccination status (vaccine uptake), vaccine hesitancy (Adult Vaccine Hesitancy Scale), and hope (Adult Hope Scale). The US grand mean hope score fell within the low-hope range. COVID-19 vaccine uptake was positively associated with hope, even after adjusting for vaccine hesitancy, gender, age, ethnicity, income, and urban vs. rural residence. The strong relationship between hope, vaccine confidence and vaccine uptake persisted across US populations at risk for low vaccine uptake. Our mediation analysis revealed that, for every unit increase in hope, the probability of being vaccinated went up by 5% points. Of this association, 52% was not mediated by vaccine hesitancy, but rather through a direct pathway from hope to vaccine uptake. Mediation analyses of US populations at risk of low vaccine uptake revealed similar findings. Hope may play an important role in vaccine uptake by reducing vaccine hesitancy and by directly enhancing vaccine uptake. Especially in populations at risk of low vaccine uptake, vaccine interventions that boost hope may augment public health efforts to increase US vaccination rates.